Non-contiguous finished genome sequence and description of Corynebacterium jeddahense sp. nov. Issue 3 (November 2014) - Edouard, Sophie; Bibi, Fehmida; Dhamodharan, Ramasamy; Lagier, Jean-Christophe; Azhar, Esam; Robert, Catherine; Caputo, Aurelia; Yasir, Muhammad; Jiman-Fatani, Asif; Alawi, Maha; Fournier, Pierre-Edouard; Raoult, Didier
Abstract Corynebacterium jeddahense sp. nov., strain JCBT, is the type strain ofCorynebacterium jeddahense sp. nov., a new species within the genusCorynebacterium . This strain, whose genome is described here, was isolated from fecal flora of a 24-year-old Saudi male suffering from morbid obesity.Corynebacterium jeddahense is a Gram-positive, facultative anaerobic, nonsporulating bacillus. Here, we describe the features of this bacterium, together with the complete genome sequencing and annotation, and compare it to other member of the genusCorynebacterium . The 2, 472, 125 bp-long genome (1 chromosome but not plasmid) contains 2, 359 protein-coding and 53 RNA genes, including 1 rRNA operon.